2017
DOI: 10.1097/iae.0000000000001494
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of Patients Discontinuing Treatment for Age-Related Macular Degeneration and Factors Associated With Visual Prognosis

Abstract: Marked deterioration in visual acuity was noted in patients discontinuing treatment, regardless of neovascular age-related macular degeneration subtypes. The presence of intraretinal fluid was associated with worse visual prognosis, suggesting that patients with intraretinal fluid should be strongly warned about their poor prognosis before they decide to discontinue treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
2
37
0
4
Order By: Relevance
“…In fact, Jeong et al reported that 77% of patients received ranibizumab more than 4 times a year and 35% of patients received ranibizumab more than 10 times a year. In other retrospective studies which used Korean hospital data between September 2009 and January 2014, a similar analysis period with our study, the average number of ranibizumab injections were reported as 4.0–4.5 per year [21, 22].…”
Section: Discussionsupporting
confidence: 70%
“…In fact, Jeong et al reported that 77% of patients received ranibizumab more than 4 times a year and 35% of patients received ranibizumab more than 10 times a year. In other retrospective studies which used Korean hospital data between September 2009 and January 2014, a similar analysis period with our study, the average number of ranibizumab injections were reported as 4.0–4.5 per year [21, 22].…”
Section: Discussionsupporting
confidence: 70%
“…The studies were mainly European and US-based, with a predominantly Caucasian population; only three reports involved patients from Asian countries. 17 , 18 , 19 The majority of studies assessed patients treated with intravitreal ranibizumab on a PRN dosing regimen, with a few more recent studies including intravitreal aflibercept or ranibizumab on a T&E regimen, Table 2 . This reflects the timing of treatment initiation of these patients, with most receiving their first anti-VEGF injection prior to 2013 (eTable 3, Supplementary materials).…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 20 , 21 Synonyms used for non-adherence included ‘non-compliance’, 22 , 23 ‘absenteeism’ 24 or ‘non-attendance’. 25 Synonyms for non-persistence included ‘treatment discontinuation/cessation’ 18 , 26 , 27 or ‘lost to follow up’…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of the problem as well as the consequences can vary considerably between the diseases. For example, a stop of treatment can quickly endanger the eyesight in nAMD [22] and proliferative diabetic retinopathy [23].…”
Section: Non-adherence and Non-persistencementioning
confidence: 99%